2018
DOI: 10.1111/jch.13162
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐dose combination therapy to reduce the growing burden of cardiovascular disease in low‐ and middle‐income countries: feasibility and challenges

Abstract: Cardiovascular disease (CVD) has become a major concern in low-and middle-income countries, which bear about 80% of the cardiovascular mortality worldwide. Curbing the burden of CVD implies the management and control of many cardiovascular risk factors that act synergistically to increase cardiovascular mortality. Such actions may require expensive polymedications in a context of limited resources. Therefore, alternative solutions for CVD prevention in low-and middle-income countries are urgently needed. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The present study clearly identified some of these factors, perhaps inferring that if specific interventions targeting each of these factors are implemented, the projected overburdened picture of CVD would be efficaciously mitigated in the Cameroonian context and beyond. Moreover, the debate of initiating a pharmacological treatment for the prevention of CVD among high-risk populations is still ongoing; a polypill made of an antihypertensive drug, a statin and inconstantly a low-dose anticoagulant is suggested to be initiated in high-risk primary prevention of CVD, but the evidence supporting this recommendation is very weak 35–37…”
Section: Discussionmentioning
confidence: 99%
“…The present study clearly identified some of these factors, perhaps inferring that if specific interventions targeting each of these factors are implemented, the projected overburdened picture of CVD would be efficaciously mitigated in the Cameroonian context and beyond. Moreover, the debate of initiating a pharmacological treatment for the prevention of CVD among high-risk populations is still ongoing; a polypill made of an antihypertensive drug, a statin and inconstantly a low-dose anticoagulant is suggested to be initiated in high-risk primary prevention of CVD, but the evidence supporting this recommendation is very weak 35–37…”
Section: Discussionmentioning
confidence: 99%
“…Attention in recent years has turned to the development and availability of a 'polypill', which is an oral tablet containing low dose aspirin, a statin, and at least one anti-hypertensive medicine to prevent CV events [195]. Such a pill is potentially seen as an affordable and cost-effective for the prevention of CVD especially in LMICs if the polypill was made available based on current public sector prices [38,40,42,143,[196][197][198][199]. Polypills have also been shown to enhance adherence, are well tolerated and reduce risk factors in both primary and secondary prevention [87,196,[200][201][202].…”
Section: Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…Table 2. Fixed-dose combination products for the prevention of cardiovascular disease that adhere strictly to the original polypill definition (adapted from [14,25,37,64]).…”
Section: Cardiovascular Diseasementioning
confidence: 99%